Congenital hallux valgus occurs in Fibrodysplasia Ossificans Progressiva and BMPR1B-associated dysplasia: an important distinction - Diksha Shirodkar; Sarah Francesca Smithson; Richard Keen; Tracy Lester; Benito Banos-Pinero; Christine Pamela Burren (BMC, 2024)
Abstract Background Fibrodysplasia Ossificans Progressiva (FOP; OMIM #135100) is an ultrarare genetic disorder characterised by congenital bilateral hallux valgus (CBHV), intermittent soft tissue swellings and progressive heterotopic ossification. We report a three-month-old girl with great toe abnormalities similar to FOP, in whom comprehensive clinical workup and genetic investigations illustrates an alternative diagnosis. Case presentation A three-month-old girl presented with CBHV. The antenatal period was unremarkable, she was born by spontaneous vaginal delivery with an uneventful subsequent course, except for maternal concern of her bent toes which received reassurance from several health professionals. Her mother's persisting concerns were explored via the internet and social media leading her to request referral to an expert bone centre for consideration of FOP. On examination, she was thriving, there was no dysmorphism, subcutaneous lumps, skeletal or extra-skeletal deformity except for shortened great toes with lateral deviation of the proximal and distal phalanges. FOP was a feasible diagnosis, for which CBHV is highlighted as an early sign. A cautionary potential diagnosis of FOP was counselled, including advice to defer intramuscular immunisations until genetic results available. Genetic investigation was undertaken through rapid whole genomic sequencing (WGS), with analysis of data from a skeletal dysplasia gene panel, which demonstrated no ACVR1variants. The only finding was a heterozygous variant of unknown significance in BMPR1B (c1460T>A, p.(Val487Asp)), which encodes a bone morphogenic receptor involved in brachydactyly syndromes A1, A2 and D and acromesomelic dysplasia 3 (only the latter being an autosomal recessive condition). Conclusion This report highlights that CBHV serves as a vital diagnostic indicator of FOP and affected infants should be considered and investigated for FOP, including precautionary management whilst awaiting genetic studies. The second educational aspect is that CBHV may not represent a generalised skeletal disorder, or one much less significant than FOP. Receptor-ligand BMP and Activins mediated interactions are instrumental in the intricate embryology of the great toe. Recognition of non-FOP conditions caused by alterations in different genes are likely to increase with new genomic technology and large gene panels, enhancing understanding of bone signaling pathways.